Modeling of the effects of athermal flow strength and activation energy for dislocation glide an the nanoindentation creep of nickel thin film at room temperature - Haseeb, A.S. Md. Abdul (Elsevier, 2006)
Nanoindentation creep behaviour of nickel at room temperature has been modeled based on the obstacle-controlled dislocation glide mechanism. Using the model, the effects of two important materials parameters viz. the activation free energy required by dislocation to overcome an obstacle without any aid from external stress, Delta F and the athermal flow strength, tau(0), which is the flow strength of solids at 0 K are systematically studied. It has been found that Delta F plays a dominant role in room temperature creep properties of nickel. The role of Delta F is particularly dominant in determining the time dependent deformation. On the other hand, role of tau(0) is more crucial in the case of instantaneous deformation. (c) 2005 Elsevier B.V. All rights reserved.